TODAY’S RESEARCH OF PHILOSOPHIC-RELIGIOUS AND FICTION PROSE BY BRITISH WRITER CLIVE STAPLES LEWIS - Lyudmila N. Efimova; Natal'ya A. Shekhireva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes the research of philosophic-journalistic and literature works by British writer of the 20th century Clive Staples Lewis conducted both by Russian and foreign academics. It provides comprehensive overview of the most important landmarks of the writer’s creative work, which are closely connected with public, political and social life of England of the said period. It should be noted that interest in researching C. S. Lewis creative work is constantly rising. It shows that ethic values that provide the foundation of his books are close and vital in the complicated and changing present day world.